SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARYAWAN DI CV BMA TECH MENGGUNAKAN METODE PROFILE MATCHING SECARA DINAMIS - M Jamalullail , Noer; Kadek Dwi Nuryana , I; Kristianto , Hery (Inovate, 2024)
Evaluation of employee performance is very important in achieving the business goals of an organization. Therefore, a decision support system is needed that can assist management in evaluating and making decisions regarding employee performance. This study uses the profile matching method with the aim of developing a web-based system that supports decision making regarding employee performance. Through the profile matching process, this system compares employee performance profiles with the criteria set by the company. Important aspects such as intellectual skills, attitudes and work habits are analyzed to measure employee performance. With the existence of this employee performance decision support system, it is hoped that management can be more coordinated in making decisions regarding employee evaluation and development. This system also has the potential to become the basis for future developments in human resource management, so as to increase overall organizational effectiveness and efficiency. Keywords: performance evaluation, profile adaptation